Barriers and Facilitators to Effective Inpatient Palliative Care Consultations: A Qualitative Analysis of Interviews With Palliative Care and Nonpalliative Care Providers. (March 2019) - McDarby, Meghan; Carpenter, Brian D.
Objective: To identify factors that hinder or facilitate the palliative care consultation team's (PCCT) successful collaboration with other providers from the perspectives of both PCCT and nonpalliative specialists. Methods: Qualitative study, including semistructured interviews with PCCT and nonpalliative care providers from various specialties at 4 Midwestern hospitals. Interviews were audio-recorded and transcribed into written text documents for thematic analysis. Palliative care consultation team (n = 19) and nonpalliative care providers (n = 29) were interviewed at their respective hospital sites or via telephone. Palliative care consultation team providers included physicians, nurse practitioners, registered nurses, social workers, and one chaplain. Specialists included critical care physicians, surgeons, hospitalists, nephrologists, oncologists, and cardiologists. Results: Six themes emerged reflecting barriers to and facilitators of successful collaboration between the PCCT and other providers. Primary barriers included attitudes about palliative care, lack of knowledge about the role of the PCCT, and patient and family resistance. Facilitators included marketing of the palliative care service and education about the expertise of the PCCT. Conclusion: In order to engage in more effective collaboration with other specialty providers, the PCCT may consider strategies including structured educational interventions, increased visibility in the hospital, and active marketing of the utility of palliative care across disciplines.